Pengaruh Kemampuan Manajerial, Perilaku Kewirausahaan dan Motivasi Terhadap Kinerja Usaha - Retno Dwi Haryanti; Grace Tiana Solovida; Rudi Suryo kristanto (ECONBANK: Journal of Economics and Banking, 2019)
Small and Medium Enterprises (SME’s) is a business activity that is able to share work and provide economic services widely to the community, and can play a role in the process of equity and increase community income, encourage economic growth, and the role in realizing national stability. The growth of SMEs requires good performance from entrepreneurs who with entrepreneurial spirit to make business in. The aims of this research is to analyze the influence of managerial skill,entrepreneurship behavior and motivation to business performance on SME’s of Food in Gesing Village, Kandangan District, Temanggung Regency. There are 100 SME owners were taken as samples in this study. The data were collected using a questionnaire. Data analysis technique used multiple linear regression analysis. The results showed that the managerial skill, entrepreneurial behavior and motivation have a positive and significant effect on the performance of SME’s of food.This shows that the better the managerial skill, entrepreneurial behavior and motivation, the higher the performance of SME’s